2007
DOI: 10.3168/jds.s0022-0302(07)71639-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Sensitivity in New Zealand Dairy Cattle

Abstract: This study quantifies the extent of within-breed sire reranking for milk production traits in a range of environments encountered within New Zealand. Character states of herds were formed within the environmental ranges of herd fat plus protein (MS) yield, summer heat load index (HLI), herd size, and altitude. Single-trait and bivariate sire models across breeds were then applied for estimation of genetic parameters and genetic correlations between extreme character states. A low degree of sire reranking occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 45 publications
2
34
0
1
Order By: Relevance
“…The genetic improvement in milk yield experienced over the last few decades is often in conflict with maintaining homeothermy . This supports the evidence reported by Bryant et al (2007): cows with high genetic merit were more susceptible to the effects of hot environments than their low genetic merit counterparts. Finally, in the American study, each test-day record was assigned to daily weather records, whereas the THI values used in this study were recorded 2 days before the sampling day.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The genetic improvement in milk yield experienced over the last few decades is often in conflict with maintaining homeothermy . This supports the evidence reported by Bryant et al (2007): cows with high genetic merit were more susceptible to the effects of hot environments than their low genetic merit counterparts. Finally, in the American study, each test-day record was assigned to daily weather records, whereas the THI values used in this study were recorded 2 days before the sampling day.…”
Section: Discussionsupporting
confidence: 81%
“…Conversely, still less information is available regarding the relationship between THI and milk fat and protein percentage. In a New Zealand study, Bryant et al (2007) reported patterns for fat and protein with a drop that occurred around the values of 50 and 60 THI, respectively. These results support the findings of this study insofar as they indicate the high sensibility of fat and protein to hot conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In North America where cows are predominantly kept indoors on total mixed rations (i.e. confinement), a different set of breeding goals has been derived compared to NZ where cows are outdoors all year round on grass (Boettcher et al, 2003;Bryant et al, 2007). Cows of NA ancestry have high milk output achieved with maximal energy inputs and have traditionally been aggressively selected for milk yield, increased body size and some phenotypic traits such as udder conformation.…”
Section: Introductionmentioning
confidence: 99%
“…The negative impact of heat stress on productivity and reproductive performance of dairy cattle and the associated economic consequences have been well documented (Fuquay, 1981;Omiński et al, 2002;Ravagnolo and Misztal, 2002;de la Casa and Ravelo, 2003;St-Pierre et al, 2003;Bryant et al, 2007;Jordan, 2003;Garcia-lspierto et al, 2007). However, most of this research has focused on hot regions while paying little attention to temperate zone countries such as Poland (Jaśkowski et al, 2005;Głuski and Michalczyk, 2008).…”
Section: Introductionmentioning
confidence: 99%